Peran Kerja Bakti Dalam Meningkatkan Kebersamaan Warga Rt 20 Rw 01 Pematang Gubernur - Diwangkara, Agustio; Achmadalena, Mirda; Wardani, Desta Andriani Kusuma; Desita, Ridha Tri; Landa, Delta R; Tambunan, Dennis Rydarto; Suwarni, Suwarni; Soleh, Ahmad (LPPM Universitas Dehasen Bengkulu, 2025)
Community service cleaning activities (kerja bakti) are one of the main programs during the Community Service Program (KKN) in RT 20, RW 01 Kelurahan Pematang Gubernur aimed at improving environmental cleanliness and strengthening community togetherness. The work is carried out regularly once a week every Sunday in each neighborhood alley. This activity actively involves residents, boarding house occupants, and KKN students. The results show that kerja bakti not only positively impacts the physical cleanliness of the environment but also enhances social solidarity and a shared sense of responsibility. Despite some challenges such as limited time and cleaning tools, the activity runs effectively due to good coordination and participation. This study highlights the importance of kerja bakti as a means to strengthen the values of mutual cooperation and social capital at the local level.